Taboo in the Next Room: Lesbian Suicide in Lillian Hellman’s The Children’s Hour (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2017)
This article argues that Lillian Hellman’s play The Children’s Hour (1934) conflates two taboos: lesbianism and suicide. In so doing, the play creates a space of irresolution that suggests an inherent instability in the process of the taboo.